Ultrasound appearance of peripheral nerves in the neck: vagus, hypoglossal and greater auricular - Curcean, Andra Diana; Rusu, Georgeta Mihaela; Dudea, Sorin Marian (Medicine and Pharmacy Reports, 2019)
Background and aim. Information in ultrasonography about reference values of nerves, particularly of those located in the neck is limited. The aim of the study is to demonstrate the feasibility of direct visualization of the vagus, hypoglossal and greater auricular nerves, testing the method on healthy volunteers and estimate the reference values for two perpendicular diameters and cross-sectional area (CSA). Methods. A prospective study was carried out on 21 healthy volunteers (12 women and 9 men), recording their demographic characteristics. A 13 MHz transducer was used on a Hitachi EUB-8500 machine. The vagus nerve was measured at the bifurcation of common carotid artery (CCA) and at the intersection of the internal jugular vein with omohyoid muscle. The hypoglossal nerve was identified as it crosses the posterolateral border of the mylohyoid muscle in the submandibular space. The auricular nerve was identified on the superficial surface of the sternocleidomastoid muscle at 1 cm from its posterior margin. The mean CSA on axial scans, nerve width and thickness were determined. The side-to-side and gender differences of the estimated reference values and their correlations with the weight, height, and body mass index (BMI) were evaluated. Results. The mean ultrasound-estimated CSA was measured for the vagus nerve at CCA bifurcation (2.14 ± 0.79 on the left 2.86 ± 1.27 on the right), vagus nerve at the level of omohyoid muscle (2.10 ± 0.06 on the left and 2.43 ± 0.08 on the right), hypoglossal nerve (1.71 ± 0.08 on the left, 1.24 ± 0.06 on the right) and greater auricular nerve (0.90 ± 0.53 on the left and 0.79 ± 0.71 on the right). The vagus nerve was significantly larger on the right side compared to the left side. Larger hypoglossal nerve was observed in men compared to women. Significant correlations were observed between weight and CSA of the greater auricular nerve. Conclusion. Direct visualization of the vagus, greater auricular nerve and hypoglossal nerves is feasible. Reference values for the size of the studied nerves at specific anatomic landmarks were established. Side, gender and body weight differences of the nerves CSA were noted.